Implementasi Strategi Marketing Mix 7P di Lembaga Satuan PNF PAUD Nurus Shibyan Kabupaten Lamongan - Istiatin, Istiatin; Widodo, Widodo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to describe and analyze the implementation of the 7P marketing mix strategy, as well as supporting and inhibiting factors in increasing the quantity of new students at PAUD Nurus Shibyan. The method used is a descriptive qualitative method with data collection techniques of in-depth interviews, participatory observation, documentation. The data analysis techniques used are data collection, data reduction, data presentation, drawing conclusions. The results obtained, namely the increase in the quantity of new students at SPS Muslimat Nurus Shibyan, cannot yet be measured because it only opened in 2023. KB Nurus Shibyan in 2022/2023 increased by 50%, but in 2023/2024 it decreased by 18%. However, when compared with 2021/2022, it has increased by 23%. Muslimat Nurus Kindergarten decreased 22% in 2022/2023, but in 2023/2024 increased 41% from the previous year. When compared with 2021/2022, there was an increase of 9.7%. In the implementation process, there are supporting and inhibiting factors for the 7P marketing mix strategy in increasing the quantity of new students.